Positive Organizational Study: A Comparison between Private and Government University Teacher - Iqbal, Farah; Shahzad, Sobia; Rattani, Sarwat Amin; Mustafa, Sadaf (Asian Journal of Social Sciences and Management Studies, 2017)
The study conducted explored the relation between Psychological Capital, General Health and Organizational Citizenship Behavior and its variation between the teachers of private and government universities of Karachi, Pakistan. Based on existing literature, following hypotheses were formulated; (1) Difference would be observed in psychological capital of private and government university teachers, (2) Difference would be observed in efficacy levels of private and government university teachers, (3) Individuals with good health will have high psychological capital, (4) Individuals with high OCB will have high psychological capital. Through convenient sampling, 261 teachers teaching at graduate-level were taken as participants. Psychological Capital Questionnaire, General Health Questionnaire and Organizational Citizenship Behavior Checklist were employed. All the hypotheses were proved when results were analyzed through SPSS. In conclusion, people having high psychological capital live healthier life and are more likely to indulge in pro-social activities and organizational citizenship behavior.